Mengatasi Kesenjangan Digital: Mewujudkan Inklusi dan Partisipasi Masyarakat Indonesia Melalui E-Government - Annaera Arastha; Bunga Almadinah; Najwa Aqilah Ferrysca; Nurdin, Nurdin (Journal Pendidikan Ilmu Pengetahuan Sosial, 2025)
This research aims to analyze how E-Government attempts to overcome the digital divide and increase community participation in Indonesia with existing obstacles. This research covers the digital divide in society, the role of government in overcoming these things through E-Government, and factors in implementing E-Government. The method used is a qualitative approach with literature analysis studies on relevant studies. The research results show that E-Government in Indonesia still needs to pay more attention to its implementation, processes and service structure because there are still obstacles in the use of E-Government which causes the absence of digital in society. The government has an important role in increasing the efficiency of e-government and reducing the digital divide in society